The Influence of Independence, Emotional Intelligence, Professional Ethics, and Organizational Culture on Auditor Performance at the Supreme Audit Agency (BPK) Representative Office in South Sumatra Province - Muhammad Hanif Ariq; Sandrayati Sandrayati; Jovan Febriantoko (Majapahit Journal of Islamic Finance and Management, 2026)
This study aims to empirically analyze the effect of Independence, Emotional Intelligence, Professional Ethics and Organizational Culture on auditor performance. The population of this study were auditors who worked at the Supreme Audit Agency (BPK) RI Representative of South Sumatra Province. The number of samples in this study were 71 auditors, using the Purposive Sampling formula method technique for sampling. This study uses a quantitative approach with the type of data in the form of primary data. The results showed that partially Emotional Intelligence and Organizational Culture had a positive effect on Auditor Performance, while partially the Independence and Professional Ethics factors had no effect on Auditor Performance. Furthermore, simultaneously Independence, Emotional Intelligence, Professional Ethics and Organizational Culture have a positive effect on auditor performance at the Supreme Audit Agency (BPK) Representative of South Sumatra Province.